The mechanical and biochemical properties of tail tendon in a rat model of obesity: Effect of moderate exercise and prebiotic fibre supplementation. (9th May 2019) - Rios, Jaqueline L.; Ko, Loretta; Joumaa, Venus; Liu, Shuyue; Diefenthaeler, Fernando; Sawatsky, Andrew; Hart, David A.; Reimer, Raylene A.; Herzog, Walter
Abstract: The worldwide trajectory of increasing obesity rates is a major health problem precipitating a rise in the prevalence of a variety of co-morbidities and chronic diseases. Tendinopathy, in weight and non-weight bearing tendons, in individuals with overweight or obesity has been linked to metabolic dysfunction resulting from obesity. Exercise and dietary fibre supplementation (DFS) are common countermeasures to combat obesity and therefore it seems reasonable to assume that they might protect tendons from structural and mechanical damage in a diet-induced obesity (DIO) model. The purpose of this study was to determine the effects of a DIO, DIO combined with moderate exercise, DIO combined with DFS (prebiotic oligofructose), and DIO combined with moderate exercise and DFS on the mechanical and biochemical properties of the rat tail tendon. Twenty-four male Sprague-Dawley rats, fed a high-fat/high-sucrose diet were randomized into a sedentary, a moderate exercise, a DFS, or a moderate exercise combined with DFS group for 12 weeks. Additionally, six lean age-matched animals were included as a sedentary control group. DIO in combination with exercise alone and with exercise and DFS reduced the Young's Modulus but not the collagen content of the rat tail tendons compared to lean control animals. However, no differences in the mechanical and biochemical properties of the rat tail tendon were detected between the DIO and the lean control group, suggesting that DIO by itself did not impact the tail tendon. It seems that longer DIO exposure periods may be needed to develop overt differences in our DIO model.